G Protein-Coupled Estrogen Receptor: Rapid Effects on Hippocampal-Dependent Spatial Memory and Synaptic Plasticity - Kumar, Ashok; Foster, Thomas C. (Frontiers in Endocrinology, 2020)
In the hippocampus, estrogen regulates gene transcription linked to neuronal growth, neuroprotection, and the maintenance of memory function [1; 2; 3]. The mechanism is likely to involve genomic regulation through classic estrogen receptor (ER) signaling cascades that influence transcription. Estrogens binding to classic nuclear ERs, alpha (ERα) and beta (ERβ), and have pleotropic effects on development, behavior, and neurophysiological functions, including synaptic plasticity and memory consolidation [4; 5; 6; 7]. In addition, ERα and ERβ can initiate activation of signaling cascades to influence the activity of G-proteins and a host of kinases, resulting in rapid changes in physiology [8; 9; 10; 11; 12; 13; 14]. In 1992, a novel 7-transmembrane G protein-coupled estrogen receptor 1 (GPER1, formerly known as G protein-coupled receptor 30-GPR30) was identified. Interestingly, GPER1 also mediates much of the rapid responses of estradiol in the adult brain, and is widely distributed in the mammalian brain including the hippocampus [15; 16; 17; 18; 19; 20]. Being a member of the G-protein coupled receptor family, GPER1 modulates second messenger signaling cascades involving Gαs- and Gαi/o-associated increase in cyclic adenosine monophosphate and phosphoinositide 3-kinase or Src protein kinase respectively [21; 22]. Activation of GPER1 is also associated with phospholipase C, and the inositol receptor and ryanodine receptor-mediated increase in intracellular calcium [15; 23]. This commentary is concentrated specifically on the possible rapid effects of GPER1 in hippocampal-dependent spatial memory function and synaptic plasticity.